การเตรียมและการศึกษาสมบัติของของเกลือของไคโตซานกับสารกำจัดวัชพืชที่เป็นกรด : รายงานฉบับสมบูรณ์ - มงคล สุขวัฒนาสินิทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
Films of the mixture of various ratios of chitosan to 2,4-Dchlorophenoxyacetic acid (2,4-D) were prepared from solution of the corresponding mixture. Releasing percentages over time of 2,4-D in water from films having different mole ratios of the chitosan to 2,4-D were determined. The films with higher ratio of chitosan 2,4-D released 2,4-D slower than the films with lower ratio of chitosan 2,4-D. The film prepared from a solution of chitosan and 2,4-D with the ratio of 20:1 controlled the release of 2,4-D up to seven days. Scanning electron microscope (SEM) showed that the films with higher ratio of chitosan have less 2,4-D on their surface. All the prepated films totally inhibited the germination of mungbean seeds (Phaseolus aureus Roxb.) within 5 days similar to the results obtained from pure 2,4-D. With the mole ratio of chitosan to 2,4-D equal to 20:1, the film however gave significantly lower germination percentages on the third and forth dates. In the germination test using a seed coating technique, the mungbean seeds coated with solutions of the mixture of 2,4-D and chitosan showed lower germination than seeds coated with solutions of the pure 2,4-D solution. The extraction study suggested that chitosan controlled the release of 2,4-D by physical interaction rather than chemical interaction.